Metoprolol prevents chronic obstructive sleep apnea-induced atrial fibrillation by inhibiting structural, sympathetic nervous and metabolic remodeling of the atria. Issue 1 (December 2017) - Sun, Li; Yan, Sen; Wang, Xiaoyu; Zhao, Shiqi; Li, Hui; Wang, Yike; Lu, Shuang; Dong, Xinwen; Zhao, Jing; Yu, Shengzhu; Li, Minghui; Li, Yue
Abstract Chronic obstructive sleep apnea (OSA) may promote the development of atrial fibrillation (AF) by inducing atrial electrical and structural remodeling as well as autonomic nerve hyperinnervation. Here, we investigated the roles of metoprolol in regulation of atrial remodeling induced by chronic OSA. A canine model of chronic OSA was established by stopping the ventilator and closing the airway for 4 h/day every other day for 12 weeks, while metoprolol (5 mg·kg-1·day-1) was continuously administered. Using that model, we observed that increases in sympathetic sprouting and atrial structural remodeling were sharply inhibited by metoprolol. Moreover, metoprolol dramatically inhibited the impairment of atrial energy metabolism by activating the Sirt1-AMPK pathway.In vitro, metoprolol significantly activated the Sirt1-AMPK pathway in intermittent hypoxic and isoproterenol-treated HL-1 cells, and the effect was abolished by the coadministration of EX-527, an inhibitor of Sirt1 activation. In summary, metoprolol protects against chronic OSA-induced atrial remodeling. Our results suggest a new and feasible treatment strategy for AF induced by OSA.